2013
DOI: 10.2527/jas.2012-5368
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy establishment and maintenance in cattle1

Abstract: A single ovulation, reciprocal embryo transfer study was used to investigate effects of oocyte competence and maternal environment on pregnancy establishment and maintenance in beef cows. Estrous cycles were synchronized in suckled beef cows and embryo donors were inseminated on d 0 (n = 810). Cows were classified on d 0 as having a small (<12.5 mm) or large (≥12.5 mm) ovulatory follicle and randomly chosen as donors or recipients to remove confounding effects of ovulatory follicle size on fertility. Embryos (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 66 publications
4
67
0
2
Order By: Relevance
“…More specifically, estradiol plays a direct role in regulating oviductal secreted glycoproteins [3] and in the regulation of the biological clock in the uterus [4]. Concentrations of estradiol peak approximately 36 h before ovulation [5] and increased preovulatory concentrations of estradiol resulted in increased fertilization success, improved embryo quality and viability [6,7], and a >60% improvement in pregnancy success [8]. Preovulatory concentrations of estradiol also have been reported to influence sperm transport [9], embryo survival [10], and the uterine environment [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, estradiol plays a direct role in regulating oviductal secreted glycoproteins [3] and in the regulation of the biological clock in the uterus [4]. Concentrations of estradiol peak approximately 36 h before ovulation [5] and increased preovulatory concentrations of estradiol resulted in increased fertilization success, improved embryo quality and viability [6,7], and a >60% improvement in pregnancy success [8]. Preovulatory concentrations of estradiol also have been reported to influence sperm transport [9], embryo survival [10], and the uterine environment [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…As previously indicated, beef or dairy females induced to ovulate small follicles after ovulation synchronization and dairy cows due to steroid catabolism (Sangsritavong et al, 2002;Vasconcelos et al, 2003) have erroneous endocrine profiles and reduced fertility (Lamb et al, 2001;Lucy, 2001;Perry et al, 2005Perry et al, , 2007. In these steroid deficient animals, previous studies in beef (Mussard et al, 2003a,b;Bridges et al, 2010Bridges et al, , 2012Atkins et al, 2013) and lactating dairy cows (Sartori et al, 2006) indicate that deficient uterine function contributes to this increased occurrence of pregnancy failure. This is not surprising given the numerous functions that estradiol and progesterone have in dictating uterine environment and function.…”
Section: Endocrine Induced Uterine Dysfunctionmentioning
confidence: 94%
“…Furthermore, Kenyon et al (2012) demonstrated that change in progesterone concentrations from d 0 to 7 was associated with pregnancy outcomes after embryo transfer on d 28, 42, and 63 of gestation and progesterone change from d 7 to 14 was associated with pregnancy outcome on d 28 and 63 of gestation. More recently, Atkins et al (2013) reported that progesterone concentrations at embryo recovery on d 7 after estrus directly influenced embryonic developmental stage. In ovariectomized ewes exogenously treated with steroids, excluding progesterone during early gestation resulted in the recovery of no embryos, reduced uterine protein synthesis, and decreased the ratio of total RNA to total DNA in the uterus .…”
Section: Hormonal Requirements For Pregnancy Establishmentmentioning
confidence: 99%
“…Cows induced to ovulate large follicles have been reported to develop larger CL compared with cows induced to ovulate small follicles (Vasconcelos et al, 2001). As the CL develops from the granulosa and theca cells of the ovulatory follicle, larger follicles tend to have more follicular cells and greater estradiol exposure which influence the developing luteal tissue after ovulation (Atkins et al, 2013). Smaller CL development in MP125 cows was expected after ovulating smaller follicles.…”
Section: Protein Amount and Bovine Ovarian Functionmentioning
confidence: 99%